2020
DOI: 10.1016/j.jobcr.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The use of Velscope to assess cellular changes occuring in oral premalignancy

Abstract: To improve visualization of suspicious lesions of the oral mucosa and to assess the accuracy of Velscope in assessing cellular changes occurring in oral premalignancy for early diagnosis. Materials and methods: In this prospective, randomized in-vivo clinical study a total of 250 patients who gave history of chewing tobacco were screened. The selection of the site of biopsy was taken based on the area of loss of fluorescence identified by the Velscope within the lesion. Routine blood investigations were done. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
7
1
1
Order By: Relevance
“…Thus, false-negative results were given by these lesions which affected the sensitivity of the device. These results of the study suggest that the Velscope cannot accurately differentiate between dysplastic and non-dysplastic lesions and are in agreement with various studies[ 23 24 ] who stated that autofluorescence has low specificity for dysplasia and malignant lesions. 45 cases of oral submucous fibrosis (OSF) were included in the present study demonstrating both autofluorescence patterns with focal areas of FVL interspersed between areas of FVR [ Table 2 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, false-negative results were given by these lesions which affected the sensitivity of the device. These results of the study suggest that the Velscope cannot accurately differentiate between dysplastic and non-dysplastic lesions and are in agreement with various studies[ 23 24 ] who stated that autofluorescence has low specificity for dysplasia and malignant lesions. 45 cases of oral submucous fibrosis (OSF) were included in the present study demonstrating both autofluorescence patterns with focal areas of FVL interspersed between areas of FVR [ Table 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…Lesions showing FVR and both autofluorescence characteristics could be due to overlap in the wavelengths of healthy oral mucosa (between 375 and 440 nm) and fibrosis (between 380 and 460 nm)[ 25 ] Physical and chemical irritation is caused by Areca nut and its metabolites which results in microtrauma and inflammation of the underlying mucosa. [ 24 26 ] The focal areas of FVL seen in OSF could be due to changes in metabolic activity of the inflamed mucosa. These lesions have a malignant transformation rate of 7–13%.…”
Section: Discussionmentioning
confidence: 99%
“…Another critical aspect of the auto-fluorescence observed in literature is the presence of false positives. The percentage of false positives is much higher in groups of patients with reactive or not dysplastic alterations because many inflammatory lesions may show LAF due to the presence of vascular inflammatory modifications (hyperemia and vasodilatation) [25]. In our study, we observed only two cases of false positives (5.71%) in s-GD and 6 (17.14%) in u-GD.…”
Section: Discussioncontrasting
confidence: 51%
“…However, the use of the device by unskilled users can lead to high false-positive results because of misinterpretation. Furthermore, it has been reported that the device should not be used at the screening stage as false positives may lead to unnecessary referrals and biopsies [ 27 , 28 ]. However, there have been reports of an increase in specificity from 8% to 10% when the FV device was used in addition to conventional oral cavity examination for the detection of epithelial dysplasia and OPMDs, even if the clinician was not specifically trained in the use of the FV device [ 29 ].…”
Section: Discussionmentioning
confidence: 99%